Integrasi Pembelajaran Pesantren dalam Membentuk Santri Interpreneurship - Mutaqin, Mohammad Toha Imammul; Khadavi, Muhammad Jadid (Paedagogie, 2026)
Islamic boarding schools play a strategic role in shaping the character of students and empowering the muslim community economically. Therefore, they are required to develop educational models that are adaptive to social and economic changes without losing their Islamic identity. This study aims to examine the integration of Islamic boarding school learning in shaping entrepreneurial students at Al-Haqiqy Islamic boarding school, Probolinggo regency. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies involving pesantren leaders, supervising teachers, student entrepreneurs, and alumni. The data were analyzed interactively through a process of reduction, presentation, and conclusion drawing, and tested for validity through source and technique triangulation. The results show that the integration of pesantren learning and entrepreneurship is not carried out through a formal curriculum, but rather through the internalization of spiritual values, the habit of independent living, the involvement of santri in pesantren business units, and the exemplary behavior of leaders, which effectively shapes the character of entrepreneurial santri based on Islamic business ethics, independence, and social responsibility. This study concludes that a value- and pesantren culture-based integrative approach is an effective and sustainable strategy in building the entrepreneurial spirit of santri.